2018
DOI: 10.3201/eid2408.171454
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology ofDiphyllobothrium nihonkaienseDiphyllobothriasis, Japan, 2001–2016

Abstract: The threat from this disease, the most common cestodiasis in Japan, is increasing because of globalization and lack of awareness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In an epidemiological study on agents of cestodosis in Japan from 2001 to 2016, Ikuno et al [4] concluded that D. nihonkaiensis infection was predominant (86% of cases) and that its incidence might increase worldwide because of marketing globalization. The present observations strongly support this conclusion, and highlights that diphyllobothriosis is no more area-restricted, as previously described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an epidemiological study on agents of cestodosis in Japan from 2001 to 2016, Ikuno et al [4] concluded that D. nihonkaiensis infection was predominant (86% of cases) and that its incidence might increase worldwide because of marketing globalization. The present observations strongly support this conclusion, and highlights that diphyllobothriosis is no more area-restricted, as previously described.…”
Section: Discussionmentioning
confidence: 99%
“…Dibothriocephalus nihonkaiensis cases were mostly described in Asia [49]. As recently published, it accounts for a vast majority of intestinal tapeworm infections in Japan, representing 86% of causative agents encountered [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuchta et al previously addressed the same question, when cases of infection with A. pacificus were diagnosed in Spain, probably due to imported fish from South America [12]. Regarding the recent French cases, it would be of interest to know where imported salmons came from exactly, as the pathogen exists not only in Japan, but also in Korea, Northern Eastern China, Northern Eastern Russia and North Pacific coast of Northern America [20], and if they were delivered to other European countries. Whether Atlantic salmon farms of Northern Europe could be contaminated with D. nihonkaiensis, although very unlikely, is another question which could be investigated, and requires life cycle adaptation, as stated above.…”
Section: What's New With Diphyllobothriosis?mentioning
confidence: 99%
“…Beyond all the epidemiological considerations, it is remarkable that the European regulation (EC, no 853/2004) requiring freezing fish destined to raw consumption is obviously not applied by all food providers. This simple measure has contributed to reduce the prevalence of infection in Northern Europe where it was highly endemic, however, this is not currently applied in Japan [20]. Whether true amateurs of sushi esteem it decreases the taste properties of the product might be considered, and could explain a lack of observance of sushi providers.…”
Section: Prevention: Don't Forget the Basics!mentioning
confidence: 99%